PENDAMPINGAN USAHA TENUN PADA KELURAHAN RANTEALANG KABUPATEN TANA TORAJA - Tangkeallo, Dian Intan; Pagiu, Chrismesi; Pundissing, Rati; Daud, Duma; Kabuaran, Reni Alik (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This service aims to provide assistance in improving the skills of weavers in introducing motifs and marketing woven fabric businesses using social media. The mentoring method used in this research includes skills training. The result of this activity is the improvement of skills and knowledge of the weavers. This will lead to the production of quality products and the development of innovative designs or motifs that respect Toraja cultural values, thus attracting consumer interest. Through this activity, weavers can exchange experiences and learn from each other. The implication of this activity is that mentoring focused on improving technical skills, knowledge, and online marketing methods is an effective strategy in developing woven fabric businesses